Pengetahuan dan Persepsi Remaja Tentang Rokok Elektrik - Wahyuni, Fitri; Choiruna, Hasby Pri; Diani, Noor (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
The use of electric cigarettes in teenagers is increasing with the circulation of informationthat electric cigarettes can be used as a tool to stop the use of conventional cigarettes. Thepurpose of this research was to determine the knowledge and perceptions of teenagers aboute-cigarettes. This research is a descriptive research with 120 respondents.Respondents weredivided into two schools, A (n=96) dan B (n=24), taken from each class which class X toclass XII. The data was taken in January 2019 using the questionnaire method. As many as61 people (50.7%) respondents had less knowledge (p-value ≤6) and as many as 64 people(53.4%) respondents had negative perceptions (p-value ≤2). The role of the government,health workers, mass media and teachers is also needed for education and regulation tochange teenagers knowledge and perceptions of e-cigarettes and to reduce new users of ecigarettes.